2015
DOI: 10.7224/1537-2073.2014-030
|View full text |Cite
|
Sign up to set email alerts
|

Prevention and Management of Infusion-Associated Reactions in the Comparison of Alemtuzumab and Rebif® Efficacy in Multiple Sclerosis (CARE-MS) Program

Abstract: Nurses played an invaluable role in the detection and management of IARs in the CARE-MS studies. Best practices for management of IARs associated with alemtuzumab include patient and caregiver education, medication to lessen IAR severity, infusion monitoring, and discharge planning.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
38
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(43 citation statements)
references
References 15 publications
4
38
0
1
Order By: Relevance
“…The main result of this study was a sustained effect of alemtuzumab after a completed 1-year treatment cycle. Finally, in a recent international study on behalf of the MSBase Study Group (published in February 2017), alemtuzumab proved superior to IFN β and fingolimod in reducing relapse rate, demonstrating similar effect to that of natalizumab 17. This cohort study compared alemtuzumab with 3 other agents, namely, natalizumab, fingolimod and IFN β 1a, in patients with RRMS treated for up to 5 years.…”
Section: Methodsmentioning
confidence: 89%
“…The main result of this study was a sustained effect of alemtuzumab after a completed 1-year treatment cycle. Finally, in a recent international study on behalf of the MSBase Study Group (published in February 2017), alemtuzumab proved superior to IFN β and fingolimod in reducing relapse rate, demonstrating similar effect to that of natalizumab 17. This cohort study compared alemtuzumab with 3 other agents, namely, natalizumab, fingolimod and IFN β 1a, in patients with RRMS treated for up to 5 years.…”
Section: Methodsmentioning
confidence: 89%
“…The most frequently reported AEs in clinical trials were infusion-associated reactions (IARs), experienced by >90% of patients, which peaked immediately following the initial alemtuzumab course and then decreased with subsequent courses [21, 22]. Few (≤3%) serious IARs were reported [9, 1113, 21, 23, 24].…”
Section: Clinical Trial Experience With Alemtuzumabmentioning
confidence: 99%
“…The day before Alemtuzumab infusion, H1 and H2 blockade should be initiated which could be applied beyond the infusion week if necessary [30,50]. An antipyretic, given 30-60 min before infusion, may help to reduce the infusion reaction.…”
Section: Alemtuzumab Infusion Managementmentioning
confidence: 99%
“…Pivotal studies not using standardized infusion procedure and methylprednisolone pre-treatment demonstrated higher levels of serum cytokines and significant more IARs after initial alemtuzumab infusions [51]. Pre-and concomitant methylprednisolone treatment incorporated into the standard infusion protocol may attenuate cytokine release syndrome and help reduce infusion-associated reactions to enhance patient tolerance [50]. This protocol is based on the procedure in pivotal studies.…”
Section: Alemtuzumab Infusion Managementmentioning
confidence: 99%
See 1 more Smart Citation